Progress in development of Membrane Fouling Control for Microalgae Filtration: a Review - Nik Nurul Ain Nabilah Razak; Muhammad Roil Bilad (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2021)
Microalgae biomass is an attractive feedstock for biofuels and other applications. Prior utilization the microalgae biomass must be harvested, a step that contributes largely to the overall energy and production costs. Membrane filtration is seen as a viable option for microalgae concentration. It is mainly attractive as primary step treating the diluted broth. However, its application is largely limited by membrane fouling that lowers overall process efficiency and productivity. This study provides an overview on the recent progress of the membrane technology particularly on technology to address the membrane fouling issue in microalgae filtration and upconcentration. Firstly, brief introduction of potential of microalgae biomass and membrane technology is provided. It followed by comprehensive overview of membrane fouling control approach. The membrane fouling control approaches are classified into optimization of operational parameters, membrane material development, hydrodynamic manipulation, improved module design and lastly module spacer development. Lastly, perspective on future research direction is also provided.